(3JdNjU GdeMUds - (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s ((3CMeO Hf CNj Whi GdeQRjahfi GdSdWGfi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi jOd GaJbGQ cd ehLhO ai GdhLhO Edjg Ydi hLhH hLhOg hHYO aEf CSGS GdYdhe GdOjfjI Ydi Yde CUhd GdOjf GdPi JMhe eSGFdg Mhd Gdjbjf s
(3BNQgG (B:s
(3hde fhQO CbhGd GdNhGQL hdG CbhGd Cgd GdSfI hGdLeGYI hdeG GJRefG JdNjU cdGeg ai gPG GdcJGH abW adjfbWY GdcdGe MGeOjf ddg hEdjg GdeQLY hGdeBH s
(3fSNI NRGFfjIs
(3dNRGfI GdSdWGf eMeO Hf GdSdWGf eQGO NGfs
(3eLOhdI heMdGI HGdPgH s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQGJ GdCUd (B:s
Keywords: (3CUhd Gdabgs